Expertise at work: New technologies, new skills, and worker impacts - Cäcilia Lipowski; Anna Salomons; Ulrich Zierahn-Weilage (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study how new digital technology reshapes vocational training and skill acquisition and its impact on workers' careers. We construct a novel database of legally binding training curricula and changes therein, spanning the near universe of vocational training in Germany over five decades, and link curriculum updates to breakthrough technologies using Natural Language Processing techniques. Our findings reveal that technological advances drive training updates, with curriculum content evolving towards less routine intensive tasks, and greater use of digital and social skills. Using administrative employer-employee data, we show that educational updates help workers adapt to new demands for their expertise, and earn higher wages compared to workers with outdated skills. These findings highlight the role of changes in withinoccupational skill supply in meeting evolving labor market demands for non-college educated workers.
Keywords: J23; J24; J31; 330; Technological Change; Vocational Training; Skill Updating